The dual roles of ginsenosides in improving the anti-tumor efficiency of cyclophosphamide in mammary carcinoma mice. (30th January 2021) - Zhu, He; He, Yi-Sheng; Ma, Jiang; Zhou, Jing; Kong, Ming; Wu, Cheng-Ying; Mao, Qian; Lin, Ge; Li, Song-Lin
Abstract: Ethnopharmacological relevance: Cyclophosphamide (CTX) is a first line chemotherapeutic agent, but often limited for its unstable therapeutic effect and serious side effects. Ginsenosides could facilitate the anti-tumor efficiency of CTX, including benefiting therapeutic effect and decreasing side effects. Aim of the study: To investigate the potential mechanism of ginsenosides on benefiting the anti-tumor efficiency of CTX. Materials and methods: Mammary carcinoma mice were applied to investigate the anti-tumor efficiency and potential mechanism of combinational treatment of ginsenosides and CTX. Therapeutic effect was evaluated based on survival rate, tumor burden, tumor growth inhibition rate, and apoptosis and histological changes of tumor tissues. Anti-tumor immunity was studied by measuring serum level of anti-tumor cytokines. Gut mucositis, one of lethal side effects of CTX, was evaluated by diarrhea degree, gut permeability and tight junction proteins expressions. Gut microbial diversity was analyzed by 16S rRNA gene sequencing, and fecal transplant and antibiotics sterilized animals were performed to evaluate the therapeutic effect of gut microbiota on tumor suppression. Results: Ginsenosides facilitated the therapeutic effect of CTX in mice, which manifested as prolonged survival rate, decreased tumor burden, as well as enhanced tumor growth inhibition rate and apoptosis. The favoring effect was related to elevation of anti-tumor immunity which manifested as the increased anti-tumor cytokines (INF-γ, IL-17, IL-2 and IL-6). Further studies indicated the elevation was ascribed to ginsenosides promoted reproduction of gut probiotics including Akkermansia, Bifidobacterium and Lactobacillus . Moreover, co-administration of ginsenosides in mice alleviated CTX-induced gut mucositis, including lower gut permeability, less diarrhea, less epithelium damage and higher tight junction proteins. Further researches suggested the alleviation was related to ginsenosides activated Nrf2 and inhibited NFκB pathways. Conclusion: Ginsenosides show dual roles to facilitate the anti-tumor efficiency of CTX, namely promote the anti-tumor immunity through maintaining gut microflora and ameliorate gut mucositis by modulating Nrf2 and NFκB pathways. Graphical abstract: Image 1